The Development of a Microcontroller Circuit Board for Practical Engineering Work - Nor Winda Binti Ismail; Mohd Sallehin Bin Abasb (INSTEP Publishing Network, 2022)
The Embedded System Application is a compulsory course for the Diploma Program in Mechatronic Engineering at Kota Kinabalu Polytechnic, Sabah. The microcontroller used for this course is the PIC16F877A PIC microcontroller. In this course, continuous assessment is tests, quizzes, the end of the chapter, and practical work. The biggest assessment percentage in this course is practical work which is 40 percent. In this course, students begin practical work by assembling all components manually, from the power supply circuit to the microcontroller circuit on the breadboard. It takes a long time for students to prepare the basic circuit each time before starting the practical work. Often, students will face errors in assembling the circuit and take time to troubleshoot and identify the problem. There is also a component failure because of assembling and disassembling the circuit. This paper presented the development of prototype board PIC16F877A to facilitate students to do practical work effectively to save time and energy and lower cost.